Management of Obstructive Sleep Apnea in Patients With Heart Failure - Wang, Youmeng; Schöbel, Christoph; Penzel, Thomas (Frontiers in Medicine, 2022)
Sleep apnea is traditionally classified as obstructive sleep apnea (OSA), which occurs when the upper airway collapses due to the relaxation of oropharyngeal musculature, and central sleep apnea occurs when the brainstem cannot stimulate breathing. Most sleep apnea in patients with heart failure (HF) results from coexisting OSA and central sleep apnea (CSA), or complex sleep apnea syndrome. OSA and CSA are common in HF and can be involved in its progression by exposure to the heart to intermittent hypoxia, increased preload and afterload, activating sympathetic, and decreased vascular endothelial function. A majority of treatments have been investigated in patients with CSA and HF; however, less or short-term randomized trials demonstrated whether treating OSA in patients with HF could improve morbidity and mortality. OSA could directly influence the patient's recovery. This review will focus on past and present studies on the various therapies for OSA in patients with HF and summarize CSA treatment options for reasons of reference and completeness. More specifically, the treatment covered include surgical and non-surgical treatments and reported the positive and negative consequences for these treatment options, highlighting possible implications for clinical practice and future research directions.